2021
DOI: 10.1002/chem.202004485
|View full text |Cite
|
Sign up to set email alerts
|

First Tribo‐Excited Chemical Reaction of a Stacked Lanthanide Coordination Polymer with an in Situ Reaction Monitor

Abstract: A tribo‐excited chemical reaction using a stacked lanthanide coordination polymer is demonstrated for the first time. The polymer is composed of a EuIII ion, hexafluoroacetylacetonato ligands, and an anthracene‐based phosphine oxide bridge. The tightly stacked structure with hydrogen bonding was characterized by X‐ray crystal structure analysis. The mechanical stimulus leads to tribo‐excited oxidation in the EuIII coordination polymer. Electron ionization mass spectroscopy and photo‐spectroscopic analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…The Eu III complex formed a dinuclear structure with stacked anthracene frameworks. Shape measurement calculations revealed that Eu adopted a square antiprism coordination geometry [7] ( S =0.676), similar to the previously reported triboluminescent lanthanide complexes [4a–c] . The distance between the anthracene frameworks is 3.9 Å; this distance is sufficient for effective dimerization reactions [6] …”
Section: Figuresupporting
confidence: 80%
See 2 more Smart Citations
“…The Eu III complex formed a dinuclear structure with stacked anthracene frameworks. Shape measurement calculations revealed that Eu adopted a square antiprism coordination geometry [7] ( S =0.676), similar to the previously reported triboluminescent lanthanide complexes [4a–c] . The distance between the anthracene frameworks is 3.9 Å; this distance is sufficient for effective dimerization reactions [6] …”
Section: Figuresupporting
confidence: 80%
“…The previous study indicate a high priority of 4 f–4 f excited state formation by tribo‐excitation [4a–b] . Recently, we were able to successfully use tribo‐excitation energy to demonstrate chemical oxidation in Eu III polynuclear complexes with hexafluoroacetylacetonato (hfa) and phosphine oxide bridges (Figure 1a) [4c] . The oxidation originated from the energy transfer from the excited Eu III ( 5 D 0 ) induced by tribo‐excitation to the lowest excited triplet state (T 1 ) in the anthracene monomer unit.…”
Section: Figurementioning
confidence: 91%
See 1 more Smart Citation
“…[31][32][33] Recently, diphosphine dioxides have been increasingly used for the construction of coordination compounds with outstanding luminescence properties. 13,22,25,30,[34][35][36][37][38][39][40][41][42][43] Most diphosphine dioxides used for preparing lanthanide complexes contain linkers that are not involved in coordination to the Ln 3+ ion. The introduction of a donor linker moiety into diphosphine dioxide is a promising approach for the preparation of potentially multidentate ligands for the formation of a saturated and rigid coordination sphere around the Ln 3+ ion (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[134][135][136][137][138][139] We focused on the role of Eu(III) excitation energy in excited state chemical reactions to achieve tribo-excitation. 140 Based on this concept, we prepared a Eu(III) coordination polymer with hfa and phosphine oxide ligands containing a reactive anthracene unit (bpa: 2,6-bis(diphenylphosphine oxide)anthracene). The stacked structure between single polymer chains was formed in the coordination polymer via hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%